Gantungan Kunci sebagai Produk Merchandise : Inovasi dan Strategi Kewirausahaan untuk Pengusaha Muda - Haniah Zuhro Ginting; M. Divanda Maulidian; Jelli Br Togatorop; Osberth Sinaga (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Key chains are popular merchandise items with significant potential in the world of entrepreneurship. This product serves not only as an accessory but also as a promotional tool and brand identity. This study examines innovations in key chain design and materials, along with entrepreneurial strategies that young entrepreneurs can use to enhance their competitiveness in the market. With a creative approach and the application of technologies like laser cutting, 3D printing, and eco-friendly materials, key chains can be transformed into more appealing and value-added products. Furthermore, digital marketing strategies, collaborations with local brands, and the implementation of personalization can boost the appeal and sales of this product. The study's findings suggest that combining product innovation with effective business strategies can aid young entrepreneurs in building sustainable and competitive businesses opportunities.